ChemInform Abstract: Direct Catalytic Asymmetric Mannich‐Type Reaction of α‐Sulfanyl Lactones. Issue 38 (30th August 2013) - Takechi, Sho; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract A catalytic asymmetric Mannich‐type reaction of α‐sulfanyl lactones and aldimines promoted by a soft Lewis acid / hard Broensted base cooperative catalyst is described.